PENINGKATAN KOMPETENSI MENGAJAR MAHASISWA PADA MATA KULIAH PENGAJARAN MIKRO MELALUI MODEL ROLE PLAY - Harini Harini (PAEDAGOGIA, 2010)
This research aims at describing: (1) the implementation Role Play model inteaching learning process on Micro Teaching subject at FKIP UNS, (2) whether or not theimplementation Role Play model improve the students’ teaching competencies. Thisresearch was conducted using Classroom Action Research consisting two cycles. Thelocation of the research was Economic Education Department BKK PTN TeacherTraining and Education Faculty UNS. The result of the research showed that Role Playmodel could improve the students' teaching competencies and personal competencies.This model provided learning experiences for the students to be more confident if theyshould teach in the class.